Fishery Resource Conservation Subsidies and Penalties in China: An Evolutionary Game Approach - Yujuan Li; Brendan Moyle; Shamim Shakur (Fishes, 2025)
In response to the ongoing depletion of fishery resources, many countries now prioritize sustainable fish stock use and ecosystem protection, balancing ecological, economic, and social goals. Fishery subsidies are key in this shift, with their impact depending on design and implementation. In 2020, China introduced marine fishery resource conservation subsidies and simultaneously phased out a 15-year policy of harmful fuel subsidies. This study uses evolutionary game theory to analyze the strategic interactions between government authorities and fishermen across four institutional scenarios, each combining different forms of subsidies and penalties. The findings suggest that a dynamic approach, incorporating both subsidies and penalties, is most effective in promoting legal fishing practices and protecting marine resources. Additionally, the study emphasizes that the effectiveness of subsidies and penalties does not necessarily increase with their scale; instead, both must be carefully calibrated to sustainable and reasonable limits.